Evaluating electrocatalytic activities of Pt, Pd, Au and Ag-based catalyst on PEMFC performance: A review - Zatil Amali Che Ramli; Jagadeesh Pasupuleti; Nik Farah Hanis Nik Zaiman; Tengku Shafazila Tengku Saharuddin; Salma Samidin; Wan Nor Roslam Wan Isahak; A.G.N. Sofiah; Siti Kartom Kamarudin; Sieh Kiong Tiong (Elsevier, 2024)
Indexed by Scopus/ERA